Phase 0 and phase III transport in various organs: Combined concept of phases in xenobiotic transport and metabolism. (August 2014) - Döring, Barbara; Petzinger, Ernst
Abstract The historical phasing concept of drug metabolism and elimination was introduced to comprise the two phases of metabolism: phase I metabolism for oxidations, reductions and hydrolyses, and phase II metabolism for synthesis. With this concept, biological membrane barriers obstructing the accessibility of metabolism sites in the cells for drugs were not considered. The concept of two phases was extended to a concept of four phases when drug transporters were detected that guided drugs and drug metabolites in and out of the cells. In particular, water soluble or charged drugs are virtually not able to overcome the phospholipid membrane barrier. Drug transporters belong to two main clusters of transporter families: the solute carrier (SLC) families and the ATP binding cassette (ABC) carriers. The ABC transporters comprise seven families with about 20 carriers involved in drug transport. All of them operate as pumps at the expense of ATP splitting. Embedded in the former phase concept, the term "phase III" was introduced by Ishikawa in 1992 for drug export by ABC efflux pumps. SLC comprise 52 families, from which many carriers are drug uptake transporters. Later on, this uptake process was referred to as the "phase 0 transport" of drugs. Transporters for xenobiotics in man and animal are most expressed in liver, but they are also present in extra-hepatic tissues such as in the kidney, the adrenal gland and lung. This review deals with the function of drug carriers in various organs and their impact on drug metabolism and elimination.